Identifying Tensions in Infrastructure Development using Public-Private Partnership (PPP) Mechanism - Suryani Eka Wijaya (Journal of Infrastructure Policy and Management (JIPM), 2021)
This research aims to identify tensions in infrastructure development using public-private partnership (PPP) mechanism. The tensions in infrastructure development are identified using a qualitative research methodology, in particular a questionnaire survey to fathom the perceived risks by associated actors and institutions, economic and financial condition, procurement processes, and the relationship between the public and private sectors. This study highlights the role of intermediate agency connecting the role of the government and the private sector. By identifying the potential and the capacity of intermediate agency to connect infrastructure development across different development agenda, the local government should be able to improve the mechanism for PPP infrastructure development scheme.